16th IEEE International Conference on Tools With Artificial Intelligence
DOI: 10.1109/ictai.2004.70
|View full text |Cite
|
Sign up to set email alerts
|

Identifying variable-length meaningful phrases with correlation functions

Abstract: Finding meaningful phrases in a document

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Our empirical results suggested that the AEMI correlation function and the MaxChildren threshold-finding method yielded more meaningful leaf clusters. In addition, by using phrases found by VPF algorithm [12], we improved performance up to 64% of interpretable clusters. We did not analyze differences among the UIHs' obtained from various users because of the large numbers of web pages used in our experiments.…”
Section: Fig 9 Uih With Words and Phrasesmentioning
confidence: 94%
See 4 more Smart Citations
“…Our empirical results suggested that the AEMI correlation function and the MaxChildren threshold-finding method yielded more meaningful leaf clusters. In addition, by using phrases found by VPF algorithm [12], we improved performance up to 64% of interpretable clusters. We did not analyze differences among the UIHs' obtained from various users because of the large numbers of web pages used in our experiments.…”
Section: Fig 9 Uih With Words and Phrasesmentioning
confidence: 94%
“…To find phrases, we used the variable-length phrasefinding (VPF) algorithm [12] because it finds more meaningful phrases than other methods [1,4]. Phrases are used to enhance the representation of a UIH.…”
Section: Evaluation Data and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations